A Straightforward Synthesis of Polyfluorinated Furan Derivatives and Their Property. Issue 12 (19th October 2018) - Agou, Tomohiro; Nemoto, Seiya; Yamada, Shigeyuki; Konno, Tsutomu; Mizuhata, Yoshiyuki; Tokitoh, Norihiro; Ebina, Ryota; Ishii, Akihiko; Hosoya, Takaaki; Fukumoto, Hiroki; Kubota, Toshio
Abstract: An abbreviated synthesis of hexafluorocyclopentane‐annulated 2, 5‐diarylfurans has been developed. 1, 2‐Dichloro‐3, 3, 4, 4, 5, 5‐hexafluorocyclopentene was converted to corresponding polyfluorinated 1, 2‐diaroylalkenes, treatment of which with P(OEt)3 afforded the polyfluorinated 2, 5‐diarylfurans. Solid‐state photo‐luminescence of the furan derivatives exhibited remarkable red‐shifts compared to fluorescence emissions in solution, probably because of intermolecular interactions in the solid state. Comparisons of the optical and electrochemical data of the fluorinated furan derivatives with those of a non‐fluorinated 2, 5‐diarylfuran suggest that the perfluorocycloalkane‐annulation effectively enhances the electron‐accepting ability of the 2, 5‐diarylfuran framework. Abstract : An abbreviated synthesis of hexafluorocyclopentane‐annulated furans has been developed. Solid‐state photoluminescence of the furans exhibited remarkable red‐shifts compared to fluorescence emissions in solution. Comparisons of the optical and electrochemical data of these furans with those of a non‐fluorinated counterpart suggest that the polyfluorocycloalkane‐annulation effectively enhances the electron‐accepting ability.